2019
DOI: 10.1002/bit.27002
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme‐mediated hydrogel encapsulation of single cells for high‐throughput screening and directed evolution of oxidoreductases

Abstract: Directed evolution of oxidoreductases to improve their catalytic properties is being ardently pursued in the industrial, biotechnological, and biopharma sectors.Hampering this pursuit are current enzyme screening methods that are limited in terms of throughput, cost, time, and complexity. We present a directed evolution strategy that allows for large-scale one-pot screening of glucose oxidase (GOx) enzyme libraries in well-mixed homogeneous solution. We used GOx variants displayed on the outer cell wall of yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 45 publications
1
29
0
3
Order By: Relevance
“…In addition, water soluble PR had a positive influence on the viability of the human skin derived fibroblasts and HaCaT cells, proving its potential for further studies related to its topological wound healing application, i.e., in the form of bioactive wound dressings. The knowledge on the chemical structure of PR and on its chemical structure–antioxidant activity relationship, obtained in this study, could be in the future transferred also in the new approach of enzymatic phenol polymerization, which has been developed recently and use the genetic manipulation to achieve the displaying of initiating the enzyme, synthesized by the cells themselves, on the cell surface, where the enzyme serves for radical polymerization of added polysaccharides with phenol moieties and encapsulation of the cell themselves [45,46]. The synthesis of PR according to recently described approach could be potentially useful for in vivo cellular therapies and it could represent a new approach for protection of cells against oxidative stress in wound healing therapies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, water soluble PR had a positive influence on the viability of the human skin derived fibroblasts and HaCaT cells, proving its potential for further studies related to its topological wound healing application, i.e., in the form of bioactive wound dressings. The knowledge on the chemical structure of PR and on its chemical structure–antioxidant activity relationship, obtained in this study, could be in the future transferred also in the new approach of enzymatic phenol polymerization, which has been developed recently and use the genetic manipulation to achieve the displaying of initiating the enzyme, synthesized by the cells themselves, on the cell surface, where the enzyme serves for radical polymerization of added polysaccharides with phenol moieties and encapsulation of the cell themselves [45,46]. The synthesis of PR according to recently described approach could be potentially useful for in vivo cellular therapies and it could represent a new approach for protection of cells against oxidative stress in wound healing therapies.…”
Section: Discussionmentioning
confidence: 99%
“…To keep the concentration of oxidant low, several methods for in-situ generation of H 2 O 2 have been reported in the literature [23][24][25]. Uyama et al and others reported a bio-enzymatic system for the polymerization of phenols using peroxidase as catalyst and glucose oxidase as in situ H 2 O 2 generation catalyst [26][27][28][29].…”
Section: Laccasesmentioning
confidence: 99%
“…Wilhelm T. S. Huck等人采用类似的策略借助单细胞微 胶囊封装系统实现了单细胞水平上的细胞因子分 泌 [148] 和mRNA定量分析 [149] . 此外, 单细胞微胶囊封装 系统为单细胞水平上的全基因组 [150] 、脂质含量 [151] 以 及蛋白酶分泌 [152] 等分析提供了平台. [159,160] .…”
Section: 机制提供了一种高通量、可靠、高分辨的策略 随后unclassified